Menjelajahi UMKM Sate Tepi Sawah di daerah Driyorejo Gresik - Husnaini, Nafa Arinal (Maliki Interdisciplinary Journal, 2024)
The processing industry sector is one of the sectors that plays an important role in the economy of a region. Warung Sate Tepi Sawah MSME is a business engaged in the culinary industry that provides a variety of processed foods. With the right steps and good management, this shop can reach a turnover of 100-300 million per month and can open branches in several cities. This research uses qualitative and descriptive methods including interviews, site observations, and data collection via the internet. Warung Sate Tepi Sawah is a successful example of a small business that can grow big through hard work, innovation, and effective marketing strategies.